Fisetin exerts neuroprotective effects in vivo and in vitro by inhibiting ferroptosis and oxidative stress after traumatic brain injury - Yang, Haiyi; Hong, Ye; Gong, Mingjie; Cai, Shihong; Yuan, Zhongwen; Feng, Senling; Chen, Qibo; Liu, Xixia; Mei, Zhengrong (Frontiers in Pharmacology, 2024)
Traumatic brain injury (TBI) is an important cause of disability and mortality, and identifying effective neuroprotective drugs and targets after TBI is an urgent public concern. Ferroptosis, an iron dependent, novel form of cell death associated with lipid peroxidation, has recently been shown to participate in secondary injury processes after TBI. Fisetin is a natural and relatively safe at general dosages flavonoid compound with neuroprotective properties. This study aimed to investigate the molecular mechanism of ferroptosis in TBI and the role of fisetin in neuroprotection by regulating ferroptosis and oxidative stress following TBI. Through in vivo experiments, a mouse model of repetitive mild closed head injury was established to determine that fisetin could reduce post-TBI injury and exert neuroprotective effects as determined by the Neurobehavioral Severity Scale score, brain water content, Nissl staining, hematoxylin-eosin staining, TUNEL staining and water maze experiment results. Fisetin was proven to be capable of inhibiting the changes in post-TBI ferroptosis proteins, activating the PI3K/AKT/NRF2 signaling pathway, and reducing oxidative stress, as confirmed by Western blotting. Via in vivo experiments, cell death models of ferroptosis were established with glutamate and erastin. As determined by MTT assay, fisetin improved the survival of cells with induced ferroptosis. The morphological alterations of ferroptotic cells were ascertained with a microscope. Fisetin similarly inhibited the changes in multiple ferroptosis-associated proteins induced by glutamate and erastin, reduced ROS and peroxidation products, and increased the level of antioxidants. In conclusion, fisetin exerts neuroprotective effects in TBI through multiple pathways, thereby alleviating tissue damage and cognitive dysfunction.